Uncertainties of estimating a town`s carbon footprint - case study El Gouna, Egipt - Banhardt, Christoph; Hartenstein, Felix (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Carbon accounting has become a valuable tool for expressing the fossil energy demand of products, organizational entities, or entire countries. About a decade ago, cities also began accounting their carbon emissions. The first major city to do so was London in 2009, stating a carbon footprint of 4.84 tCO2eq/(Lear*capita) for 2008. Nowadays, multiple rankings compare the carbon emissions of cities.
Keywords: carbon accounting; carbon emission; carbon footprint; city emissions; dwutlenek węgla; emisja dwutlenku węgla; zanieczyszczenie miasta